Hukum Dan Usaha Remaja Masjid Mukhtarul Arifin Perumahan Cipta Asri Kelurahan Tembesi Kota Batam - Ukas Ukas; Moh. Andika Surya Lebang; Padrisan Jamba; Risca Azmiana (Prosiding, 2023)
The material provided in this coaching is divided into 2 groups, namely the legal group and the business group aimed at "Youth / Young Generation". The coaching material given to the legal group is to provide an introduction and / or understanding of the existing arrangements (rules of law), because after all he will be the next generation of religious leadership, nation and state. To not be wrong, then from an early age given an understanding of the rule of law that exists in the midst of the nation and state society. With the hope that with a brief education / training like this, he will understand. The debriefing material provided to business groups is to provide an introduction and/or understanding and invite adolescents/young people from an early age to develop their talents in business. To understand the importance of living independently in the future, of course in this case how to do good business, full of honesty and justice, and understand how to develop.